Hands-on Kubernetes on Azure : use Azure Kubernetes Service to automate management, scaling, and deployment of containerized applications /: use Azure Kubernetes Service to automate management, scaling, and deployment of containerized applications. (2021) - Franssens, Nills; Gopalakrishnan, Shivakumar; Lenz, Gunther
No abstract available